2017
DOI: 10.5138/09750185.2050
|View full text |Cite
|
Sign up to set email alerts
|

Role of protective Pelargonium Sidoides root extract and Curcumin on Mushroom poisoning: An Experimental study in rats

Abstract: <p>Phalloidin is a cyclic heptapeptide containing cysteine amino acids. The toxicity of phallodin is attributed to the sulfur atom of the sulfur in the indole ring of the molecule and it is responsible for acute gastroenteritis occurring during the initial period of poisoning. Pelargonium sidoides, reinforcing the immune system, antiviral, has antibacterial properties as well as antioxidant properties.The aim of this study is to investigate the protective role of Pelargonium sidoides and Curcumin against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This may protect the liver cells from damage and improve the function after damage. Unsal et al [66] revealed that the antioxidant and detoxification properties of P. reinforme/sidoides extract against mushroom poisoning is through reduction of malondialdehyde, increasing Paraoxonase levels and regulating purine metabolism thus reducing ROS. The extract of P. reinforme/sidoides also significantly decreased levels of liver enzyme markers (AST, ALT, ALP and GGT) indicating that the extract possessed a curative effect.…”
Section: Discussionmentioning
confidence: 99%
“…This may protect the liver cells from damage and improve the function after damage. Unsal et al [66] revealed that the antioxidant and detoxification properties of P. reinforme/sidoides extract against mushroom poisoning is through reduction of malondialdehyde, increasing Paraoxonase levels and regulating purine metabolism thus reducing ROS. The extract of P. reinforme/sidoides also significantly decreased levels of liver enzyme markers (AST, ALT, ALP and GGT) indicating that the extract possessed a curative effect.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have antioxidants, free radical scavengers and anti-toxic properties. 16 , 23 , 131 - 132 …”
Section: Discussionmentioning
confidence: 99%